University Social Responsibility and its Application to the Management of Administrative Tools in the Provisional Deprivation Center of Freedom Sector Guayaquil - Ecuador, a Reflexive Humanistic Look - Peláez Freire, José Miguel (2018)
The scope of the research is of an explanatory nature, since not only the characteristics visible to the naked eye are recreated in the training process, but also the behavior, behaviors and transformations evidenced in the subjects are explained, contributing to the knowledge management in administrative tools to build skills, management skills in inmates deprived of freedom, from a humanistic approach. Person and company are not currently synonymous with generating changes, the company is located in the first place leaving aside the value of the human being and its influence as a value in the company. It is intended to have a more human look at the business organizational environment, starting from a formative experience with people deprived of freedom, providing them with tools that will allow them in the future to do business from a more human perspective.